Cardiac Sympathetic Denervation Mitigated Ischemic Cardiomyopathy Progression in a Rat Model of Sleep Apnea - Maximin Détrait; Jonathan Gaucher; Emma Billoir; Sophie Bouyon; Emeline Lemarié; Stéphanie Paradis; Guillaume Vial; Florent Chuffart; Côme Pasqualin; Fabien Hubert; Francesca Rochais; Stéphane Doutreleau; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background Ischemic cardiomyopathy with comorbid obstructive sleep apnea syndrome is associated with worse long‐term outcomes. Intermittent hypoxia (IH), a key feature of obstructive sleep apnea, exacerbates sympathetic activity, hastening cardiac dysfunction and remodeling in ischemic cardiomyopathy rat models. This study explores whether targeted cardiac sympathetic denervation (CSD) can limit IH‐induced progression of ischemic cardiomyopathy. Methods Male Wistar rats underwent CSD, through ablation of the left middle cervical and stellate ganglions, and simultaneously myocardial infarction, via permanent left coronary artery ligation. Three days post surgery, rats were exposed to IH (21%–5% fraction of inspired O2, 60‐second cycle, 8 hours/day) or normoxia. At 6 weeks, calcium transient, sarcomere shortening, and adrenergic reserve in response to isoproterenol (100 nmol/L) were assessed in isolated cardiomyocytes. At 14 weeks, sympathovagal balance, cardiac function, and remodeling were evaluated. Results Post myocardial infarction, CSD prevented IH‐induced blunting of cardiomyocyte response to isoproterenol challenge and reduced cardiac sympathetic activity. In hypoxic animals, CSD reduced post‐myocardial infarction alterations in long‐term ejection fraction and mitigated cardiomyocyte hypertrophy and apoptosis. Transcriptomic analysis unveiled that CSD triggered biological processes related to cardiac repair and regeneration. Immunohistochemistry further supported these findings, demonstrating increased cardiomyocyte proliferation in the hypoxic group, as indicated by elevated Ki67 expression colocalized with MF20 markers. Conclusions Our data demonstrate that CSD prevents IH‐induced sympathetic hyperactivity, depletion of cardiac adrenergic reserve, and deterioration of cardiac function in a rat model of ischemic cardiomyopathy. This study highlights the intricate interplay between sympathetic activity and hypoxia in cardiac regeneration and underscores the importance of managing sympathetic hyperactivity in ischemic cardiomyopathy, particularly in the context of comorbid obstructive sleep apnea.